Examining the Discursive Construction of Tolerance towards Lesbian, Gay, Bisexual, and Transgender (LGBT) in Malaysia - HSIN NIE, LING (UNIMAS INSTITUIONAL REPOSITORY, 2023)
This study examined tolerance towards Lesbian, Gay, Bisexual, and Transgender (LGBT) individuals among Malaysians through self-reports and analysis of LGBT representation via a discourse historical approach. Questionnaire data were collected from 413 participants living in Malaysia while interviews were conducted with 20 participants (14 heterosexuals and 6 LGBT). The questionnaire results showed that the younger generation in their twenties with higher education and have personal connection with LGBT tend to report greater tolerance towards LGBT individuals. The discursive analysis of interviews revealed that most of the heterosexual participants are able to accept it if their friends and colleagues are LGBT but not if their religious leader and own children are LGBT. The heterosexual participants agreed that LGBT individuals should deserve to have the same rights in society but they neither openly support legalisation of same-sex marriage nor oppose it. On the other hand, the LGBT participants stated that they chose to come out to their friends or siblings rather than their parents who are less tolerant towards the idea of LGBT. The interviews produced a more in-depth understanding of the participants' thoughts, beliefs and experiences that underlie their attitudes towards LGBT, but the results were similar to the questionnaire results, indicating that the data collection technique does not substantially influence results on LGBT.